Inhibitors for ubiquitous deployment of services in the next-generation network. - Gurbani, Vijay K.; Xian-He Sun.; Brusilovsky, Alec.
The next-generation network is characterized by the merging of the Internet, telecommunications, and information technology. As envisioned some six years ago, the NGN was to revolutionize the lives of its users by providing them the best of the services of the PSTN and the Internet, written rapidly by IT programmers. Service providers were to be similarly affected by the increase in revenues paid by the users of these new services. Equipment vendors would have a difficult time keeping inventories of the NGN infrastructure. The truth has been somewhat different. In this article we characterize a set of inhibitors - technical, regulatory, and business-related - that are affecting the ubiquitous deployment of NGN services.
Keywords: Internet; PSTN; next-generation network; service providers; ubiquitous deployment